Traumatic brain injury-associated epigenetic changes and the risk for neurodegenerative diseases - Smolen, Paul; Dash, Pramod K.; Redell, John B. (Frontiers in Neuroscience, 2023)
Epidemiological studies have shown that traumatic brain injury (TBI) increases the risk for developing neurodegenerative diseases (NDs). However, molecular mechanisms that underlie this risk are largely unidentified. TBI triggers widespread epigenetic modifications. Similarly, NDs such as Alzheimer’s or Parkinson’s are associated with numerous epigenetic changes. Although epigenetic changes can persist after TBI, it is unresolved if these modifications increase the risk of later ND development and/or dementia. We briefly review TBI-related epigenetic changes, and point out putative feedback loops that might contribute to long-term persistence of some modifications. We then focus on evidence suggesting persistent TBI-associated epigenetic changes may contribute to pathological processes (e.g., neuroinflammation) which may facilitate the development of specific NDs – Alzheimer’s disease, Parkinson’s disease, or chronic traumatic encephalopathy. Finally, we discuss possible directions for TBI therapies that may help prevent or delay development of NDs.